Composite sustainable development indicators in case of 28 European Union member states - Kozma Dorottya Edina; Козма Д. Е. („RIK-U” Kft., 2020)
Abstract. The 2030 Agenda framework strategy uses indicators that are difficult to interpret because of their size and their progress. Within the strategy 244 indicators have been created covering the three aspects of sustainable development. The aim of my study is to develop composite indicators from the 2030 Agenda’s sustainable development indicators. With this method I can reduce the size of the database and at the same time, drawing conclusions becomes easier and faster. My assumption is that this composite indicator system can be created and further utilized in future researches.
https://kmf.uz.ua/wp-content/uploads/2020/09/final_1_kotet-foldrajzfkonf-2020-07-14.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008119
Keywords: SDGs; composite indicators; European Union; sustainable development